Impact Properties of Hemp Natural – Glass Fibers Hybrid Polypropylene Sandwich Composites - Lies Banowati; I Putu Udawan Pertama (Indonesian Journal of Applied Research (IJAR), 2023)
One way to improve the mechanical properties of composite structures is by hybridizing natural and synthetic fibers. Besides that, combined with sandwich structure composites consists of two relatively strong, thin, and stiff faces separated by a core, for example, balsa, foam, and honeycomb, a relatively thick lightweight. This research develops sandwich composites for structures that have able to withstand high loads and modulus-to-weight ratios but can absorb impacts through impact tests by utilizing the raw material of jute natural fiber, which is abundant in Indonesia so that this research study can predict the effect of variations in the hybridization of hemp natural fiber and the combination of hemp natural fiber with e-glass using polypropylene core sandwich composites by using hand lay-up and vacuum bagging methods. The current impact test results show that the hemp natural-e-glass fibers hybrid sandwich composites get a higher impact strength with a value of 0,019 J/mm² than the hemp-PP honeycomb hybrid sandwich composite with a value of 0,013 J/mm². It shows that by combining e-glass fiber in the composite, it can increase its impact strength and can be a lightweight structural material as being a new alternative material of jute and e-glass natural fiber hybrid sandwich composites with polypropylene cores to substitute conventional materials such as metals which is potential for applications in the automotive, building, and unmanned aerial vehicle industries.